Teknik Sulam Sebagai Desain Permukaan Pada Jaket Crop Denim - Fitra Sari; Handayan Sarah Rum (Pusat Penerbitan LP2MPP ISI Denpasar, 2023)
The design of this is a surface design with rose-colored embroidered techniques and doves. The purpose of this design was to enrich colors, textures, and designs on crop denim jackets. The methods used are: 1) Exploration involves a type of thread and color, as well as three - dimensional - shaped embroidery on which the surface design is based. 2) The concept of designing surface designs with consideration of materials, processes, methods, ergonomy, security, comfort, aesthetic elements, philosophy, meaning, and future opportunities. 3) A laborious, laborious process. The result of this design is 1) Exploration is done both directly and indirectly. 2) The design of the surface of verbal forms into visual shapes by considering the value of the kriya art. 3) The realization of the work was realized as a practical function.